Aeroelastic-photovoltaic ribbons for integrated wind and solar energy harvesting. (11th July 2018) - Chatterjee, P; Bryant, M
Abstract: This letter investigates the energy harvesting capabilities of a novel hybrid wind and solar transduction device. The proposed device is an inverted-U shaped structure with a pair of piezoelectric benders connected by a flexible, tensioned photovoltaic ribbon. The tensioned photovoltaic ribbon member undergoes aeroelastic flutter limit cycle oscillations (LCOs) at low wind speeds, leading to time-varying tension forces applied to the piezoelectric benders, producing cyclic deflections and output voltage. Experimental characterization of the proof of concept energy harvester indicates that it is possible to obtain several milliwatts (mW) of power using the centimeter scale device, with an output power of ∼12.1 mW at a combination of 12 m s −1 wind speed and 100 W m −2 of solar irradiance, for indirect solar applications. It is shown here that an optimal combination of applied tensile preload and preset angle of attack exists which produces the highest wind power output of the system. An explanation of this behavior is also provided through the analysis of data collected on the photovoltaic ribbon velocity, piezoelectric voltage signals, and high-speed imagery, providing further insight to the motion kinematics of the highly nonlinear system response. Interestingly, the solar power output has been observed to remain invariant with increasing vibration velocity. This suggests that the gain in solar power efficiency from vibration-induced convective cooling negates any losses from the deflected incidence angle of the photovoltaic ribbon. These results illustrate that there is a negligible performance penalty in adding wind energy harvesting capability to the solar cells with this device concept.